Teaching Ecosystems with an ict-Mediated Bioethical Approach - Barrera Vanegas, Marlén Rocío; Calderón Rojas, Giovani; Victoria González, Christian (Rastros Rostros, 2017)
Introduction: This article shows the research results of teaching ecosystems with a bioethical approach, mediated by information and communication technologies (ict), as a didactic learning strategy to be applied in the subject of Natural Sciences for eighth-grade students from the educational institution Guillermo Cano Isaza in Ciudad Bolívar, Bogotá to take bioethical principles in. For this purpose, we worked with a group of 36 eighth-grade students using an alternative method from an ict-mediated bioethical approach. Materials and methods: A type of mixed research in the framework of the socio-critical paradigm using quantitative and qualitative instruments. For ten weeks, the experimental group participated in an online course designed on the Moodle platform to support the proposal. Results: It is verified that the grasping of bioethical principles through ict is more viable and highly significant; students become more interested in both the Science class and the care and preservation of the environment. Conclusions: Addressing curricular themes from bioethics mediated by virtual environments can be part of favorable alternative learning dynamics and promote the integration of subjects.